Bullying Prevention in Schools: Evaluating Social, Economic, and Technological Interventions - Handayani, Annisa Awalia; Falah, Fathi (Journal of Health Literacy and Qualitative Research, 2023)
Bullying among adolescents remains a critical public health and educational concern, impacting mental well-being, academic performance, and social development. This study explores the multifaceted nature of bullying, focusing on its psychological, social, and economic determinants, as well as the effectiveness of intervention strategies. A systematic review of literature from academic databases such as PubMed, Scopus, and PsycINFO was conducted, selecting peer-reviewed studies published in the last decade. The results highlight the protective role of family support and positive school climates in mitigating bullying-related distress. Economic disparities significantly influence bullying prevalence, with students from lower-income backgrounds facing heightened risks. Effective intervention strategies include restorative justice practices, social-emotional learning programs, and anonymous reporting platforms. Cross-national comparisons reveal that community-based interventions, such as Finland’s KiVa program, yield more sustainable outcomes by fostering an inclusive school culture. The discussion underscores the need for comprehensive policies that integrate school-wide prevention programs, parental involvement, and mental health support. Future research should focus on longitudinal studies to assess the long-term effects of bullying and the scalability of different intervention models. A multi-stakeholder approach involving educators, policymakers, and parents is essential to creating a safer educational environment. Addressing bullying through targeted interventions and policy reforms will contribute to improved student well-being and academic success.